Validation of polylactic acid polymer as soft tissue substitutive in radiotherapy - Pereira, Dirceu Dias; Cardoso, Simone Coutinho; da Rosa, Luiz A.R.; de Souza, Felipe M.L.; de Sousa, Juan V.M.; Batista, Delano V.S.; Boiset, Gisell Ruiz; Wolff, Wania; Gonçalves, Odair Dias (Radiation physics and chemistry (Oxford, England : 1993), 2021)
We report the experimental study on the physical and radiation properties of polylactic acid polymer (PLA-C3H4O2) combined with Monte Carlo simulations for application in radiotherapy. The suitability of PLA for phantoms construction as a substitute for soft human tissue in MeV photon radiation dosimetry and therapy is discussed. The elemental composition and radiation properties are described as recommended by ICRU 44. In addition, Hounsfield unit (HU), mass attenuation coefficient, mass stopping power and tissue phantom ratio were determined. Previous works on this subject presented mainly the properties of the raw material formula, neglecting above all the effects of the printing matrix and commercial raw materials used for PLA's production. The present upon irradiation properties of polylactic acid polymer were contrasted to those known of solid water and attested the viability and performance of PLA to bio-mimic soft tissue. The experimental and simulated data demonstrate the adequacy of PLA to printed phantoms provided that the printer infills result in a density of 1.05–1.09 g/cm3. •Investigation of physical and radiation properties of polylactic acid polymer.•The radiation properties are not affected by the addition of dyes in some PLA.•Suitability of PLA for phantoms construction as a substitute for soft human tissue.•PLA is adequate for 3D printing of RT phantoms.